Preparation method of electron transport layer for high-efficiency perovskite solar cells

The preparation of nitrogen-doped tin oxide thin film as the electron transport layer of perovskite solar cells through chemical bath deposition method solves the shortcomings of perovskite solar cells in terms of photoelectric conversion efficiency and long-term stability, and achieves higher photoelectric conversion efficiency and better stability.

CN114122264BActive Publication Date: 2025-05-02WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111282670.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-05-02
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

Existing perovskite solar cells have shortcomings in photoelectric conversion efficiency and long-term stability, especially in terms of open circuit voltage loss and electroluminescent external quantum efficiency.

Method used

A nitrogen-doped tin oxide film was prepared in one step as an electron transport layer by chemical bath deposition. The hydrolysis rate was controlled by doping NH4Cl and HCl in the Sn4+ dilution to obtain SnO2 particles with smaller and uniform particles, and the conductivity of the electron transport layer and the interfacial charge extraction ability were improved.

Benefits of technology

It achieves smaller open circuit voltage loss and higher photoelectric conversion efficiency, improving the long-term light stability of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114122264B_ABST
    Figure CN114122264B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of an electron transport layer for an efficient perovskite solar cell. An FTO glass after UV treatment is immersed in Sn 4+ dilution solution and sealed, heated in a forced air drying oven until a distinct Tyndall effect occurs, taken out and washed after sufficient cooling with running water, and annealed to obtain an SnO2 electron transport layer; the Sn 4+ dilution solution is prepared by the following method: anhydrous SnCl4 and deionized water are mixed at a volume ratio of 3:7, stirred at 0-5 °C for 12-24 h, and the obtained mixed solution is diluted 18-20 times with deionized water; 180-1020 mg of NH4Cl is added to 100 mL of the dilution solution, and then an appropriate amount of HCl is added, and it is stored in a refrigerator for later use; in the present invention, by doping NH4Cl in the Sn 4+ dilution solution and adding HCl to control the hydrolysis rate and other means, SnO2 particles with smaller and uniform particles are obtained, the quality of the SnO2 thin film is improved, the conductivity of the electron transport layer is increased, and the extraction and transport of interfacial charges at the SnO2 / Perovskite interface are enhanced, reducing interfacial non-radiative recombination, improving the photoelectric conversion efficiency of the perovskite photovoltaic device and reducing hysteresis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for preparing an electron transport layer of a high-efficiency perovskite solar cell. Background Art

[0002] In the past few years, organic-inorganic hybrid perovskite solar cells (PSCs) have made rapid progress, and the continuous improvement of photoelectric conversion efficiency (PCE) has made it possible to compete with silicon solar cells, which currently dominate photovoltaic cells. As one of the most promising photovoltaic technologies, perovskite solar cells have unique advantages over other similar products, such as easy manufacturing, low production cost, and compatibility with flexible electronic products.

[0003] The performance of perovskite solar cells is largely affected by the device structure, perovskite active layer materials, charge transport layers and interfaces, which are also the most widely studied areas. Currently, from the perspective of device structure, perovskite solar cells can be mainly divided into two categories, namely conventional type (nip) and inverted type (pin). In the above two structures, the perovskite absorption layer is sandwiched by the charge transport layer to form a sandwich structure. Among them, the conventional type (nip) is the pioneer of perovskite solar cells, and many experts and scholars are committed to improving its PCE and long-term stability.

[0004] In conventional perovskite solar cells, metal oxides with n-type semiconductor properties are usually selected as electron transport layer (ETL) materials, such as TiO2, SnO2, ZnO, etc.

[0005] So far, in terms of photoelectric conversion efficiency, SnO2-based perovskite solar cells have surpassed 25%, reaching the record efficiency based on TiO2, and the stability of the device has also been greatly improved. In addition to the perovskite absorption layer, the improvement in performance is mainly due to the optimization of the photoelectric properties of the SnO2 electronic layer, such as conductivity, work function, defect density, and the interfaces involved.

[0006] Tin oxide as ETL not only has a suitable energy level match with perovskite, but also has the advantage of low-temperature synthesis. Among various deposition methods, ETLs prepared based on SnO2 nanoparticles showed the best performance. However, PSCs prepared based on SnO2 nanoparticles still showed relatively low electroluminescence external quantum efficiency (EQE) values ​​and high open circuit voltage (V OC ) defects. Therefore, efforts are made to minimize the photovoltage loss at the ETL / perovskite interface, thereby minimizing V OC Attrition strategy is critical. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing an electron transport layer of an efficient perovskite solar cell, in which a nitrogen-doped tin oxide thin film is prepared as an electron transport layer in one step by a chemical bath deposition method. The perovskite solar cell prepared in this way has a smaller open circuit voltage loss and a higher photoelectric conversion efficiency, as well as better light stability.

[0008] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0009] A method for preparing an electron transport layer of a high-efficiency perovskite solar cell comprises the following steps:

[0010] The UV treated FTO glass was immersed in Sn 4+ The SnO2 electron transport layer is obtained by sealing the diluted solution and heating it in a forced air drying oven until an obvious Tyndall effect is produced. The SnO2 electron transport layer is obtained after being fully cooled with running water and then taken out for cleaning.

[0011] According to the above scheme, the Sn 4+ The dilutions were prepared as follows:

[0012] Anhydrous SnCl4 and deionized water were mixed in a volume ratio of 3:7, stirred at 0-5°C for 12-24h, and the resulting mixed solution was diluted 18-20 times with deionized water;

[0013] Add 180-1020 mg NH4Cl to 100 mL of diluent, then add appropriate amount of HCl and refrigerate for later use.

[0014] According to the above scheme, the temperature of the blast drying oven is 80-100°C and the heating time is 1.5-2.5h.

[0015] According to the above scheme, the annealing temperature is 150-170°C and the annealing time is 0.5-1.5h.

[0016] When using chemical water bath deposition to prepare SnO2 thin films, the existing technology is based on Sn 2+ As a tin source, its deposition process involves two steps: oxidation and hydrolysis. 2+ The oxidation of SnO2 is uncontrollable. The present invention directly utilizes a tetravalent tin source to directly prepare the SnO2 electron transport layer, and its quality is easier to control.

[0017] The present invention is Sn 4+ By doping NH4Cl in the diluent and adding HCl to control the hydrolysis rate, smaller and more uniform SnO2 particles were obtained, which improved the quality of SnO2 film, the conductivity of the electron transport layer, and the extraction and transport of charges at the SnO2 / Perovskite interface, reducing interfacial non-radiative recombination, improving the photoelectric conversion efficiency of perovskite photovoltaic devices and reducing hysteresis.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The preparation process is simple and highly reproducible;

[0020] With higher open circuit voltage V OC and higher photoelectric conversion efficiency and smaller hysteresis;

[0021] Has better long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : Scanning electron microscope images of SnO2 nanofilm materials obtained in Examples 1 and 3;

[0023] Figure 2 : Scanning electron microscope images of the perovskite films obtained in Examples 1 and 3;

[0024] Figure 3 : Steady-state output diagram of the perovskite solar cells obtained in Examples 1 and 3 at the maximum power point. DETAILED DESCRIPTION

[0025] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0026] In a specific embodiment, Sn 4+ The dilutions were prepared as follows:

[0027] Anhydrous SnCl4 and deionized water were mixed in a volume ratio of 3:7, stirred at 0-5°C for 12-24h, and the resulting mixed solution was diluted 18-20 times with deionized water (labeled as solution A);

[0028] Take 100 mL of solution A, add 180-220 mg NH4Cl and 1.5-2.5 mL HCl, mix well and treat with ultrasound, and refrigerate for later use (labeled solution B).

[0029] Take 100 mL of solution A, add 480-520 mg of NH4Cl and 1.5-2.5 mL of HCl, mix well and treat with ultrasound, and refrigerate for later use (labeled solution C).

[0030] Take 100 mL of solution A, add 980-1020 mg of NH4Cl and 1.5-2.5 mL of HCl, mix well and treat with ultrasound, and refrigerate for later use (labeled solution D).

[0031] Embodiment 1:

[0032] 1) Wipe the surface of the glass substrate etched by the femtosecond laser with a dust-free cloth dipped in detergent to remove surface stains until the surface of the substrate can be wetted by water, then put the substrate into a container filled with detergent, deionized water and ethanol for 30 minutes each to ensure that the surface of the glass substrate is clean and free of stains. Then, blow dry the glass surface with an air gun, wrap it with a dust-free cloth for standby use, and put it in a UV cleaning machine for 15 minutes before use.

[0033] 2) Preparation of SnO2 electron transport layer: Take solution A and put it into a clean glass container, put in the cleaned FTO glass and seal it; heat it in an 80℃ oven until an obvious Tyndall effect occurs, cool it with running water, take it out and clean it to remove excess SnO2 particles on the surface, then wipe the back of the glass substrate to remove the SnO2 particles attached to the back, blow it dry with an air gun, and place it on a hot table to anneal at 110℃ for 0.5h.

[0034] 3) The perovskite active layer was prepared by anti-solvent method. In this experiment, (FAPbI3) was used. 0.95 (MAPbBr3) 0.05 System. The specific formula is: 0.07M MABr, 0.07M PbBr2, 0.5M MACl, 1.4M FAI and 1.53M PbI2, dissolved in a mixed solvent of 1mL DMF / DMSO (v / v=8:1), and fully shaken. Take 35μL of perovskite precursor droplets on a glass substrate, and use a pipette tip to make it evenly spread, but not touch the glass substrate. The present invention adopts a one-step method, and the spin coating step is divided into two steps. The first step has a rotation speed of 1000rpm and a time of 10s; the second step has a rotation speed of 5000rpm and a time of 30s (the acceleration is 2000rpm / s). In the tenth second of the second step, 110μL of ethyl acetate (EA) solution is added as an anti-solvent to obtain a transparent bright orange liquid film. Subsequently, the substrate is placed on a 100°C hot stage for annealing for 1h.

[0035] 4) Weigh 91.4 mg Spiro-OMeTAD, dissolve it in 1 mL chlorobenzene (CBZ), add 35.1 μL t-BP, 11.4 μL cobalt ion solution (300 mg Co-TFSI dissolved in 1 mL acetonitrile (CAN)), 21 μL lithium ion solution (520 mg Li-TFSI dissolved in 1 mL ACN), and shake thoroughly. After the substrate cools to room temperature, 35 μL of the solution is evenly coated on its surface at a speed of 4000 rpm, an acceleration of 2000 rpm / s, and a time of 20 s.

[0036] 5) Preparation of metal back electrode: A layer of 80nm Au electrode is evaporated on the surface by an evaporator to form a complete device.

[0037] The perovskite solar cell prepared in this experiment was tested under the conditions of one light intensity and a test area of ​​0.11 cm 2 The test light source is AAA level. The results show that the battery reverse scanning photoelectric conversion efficiency is 19.39%, with an open circuit voltage of 1057mV and a short circuit current of 24.15mA / cm 2 , the fill factor is 0.74; the forward scanning photoelectric conversion efficiency of the battery is 8.81%, with an open circuit voltage of 815mV and a short circuit current of 24.10mA / cm 2 , the filling factor is 0.44.

[0038] Embodiment 2:

[0039] 1) Wipe the surface of the glass substrate etched by the femtosecond laser with a dust-free cloth dipped in detergent to remove surface stains until the surface of the substrate can be wetted by water, then put the substrate into a container filled with detergent, deionized water and ethanol for 30 minutes each to ensure that the surface of the glass substrate is clean and free of stains. Then, blow dry the glass surface with an air gun, wrap it with a dust-free cloth for standby use, and put it in a UV cleaning machine for 15 minutes before use.

[0040] 2) Preparation of SnO2 electron transport layer: Take solution B and put it into a clean glass container, put in the cleaned FTO glass and seal it; heat it in an 80℃ oven until an obvious Tyndall effect occurs, cool it with running water, take it out and clean it to remove excess SnO2 particles on the surface, then wipe the back of the glass substrate to remove the SnO2 particles attached to the back, blow it dry with an air gun, and place it on a hot table to anneal at 170℃ for 1.5h.

[0041] 3) The perovskite active layer was prepared by anti-solvent method. In this experiment, (FAPbI3) was used. 0.95 (MAPbBr3) 0.05 System. The specific formula is: 0.07M MABr, 0.07M PbBr2, 0.5M MACl, 1.4M FAI and 1.53M PbI2, dissolved in a mixed solvent of 1mL DMF / DMSO (v / v=8:1), and fully shaken. Take 35μL of perovskite precursor droplets on a glass substrate, and use a pipette tip to make it evenly spread, but not touch the glass substrate. The present invention adopts a one-step method, and the spin coating step is divided into two steps. The first step has a rotation speed of 1000rpm and a time of 10s; the second step has a rotation speed of 5000rpm and a time of 30s (the acceleration is 2000rpm / s). In the tenth second of the second step, 110μL of ethyl acetate (EA) solution is added as an anti-solvent to obtain a transparent bright orange liquid film. Subsequently, the substrate is placed on a 100°C hot stage for annealing for 1h.

[0042] 4) Weigh 91.4 mg Spiro-OMeTAD, dissolve it in 1 mL chlorobenzene (CBZ), add 35.1 uL t-BP, 11.4 uL cobalt ion solution (300 mg Co-TFSI dissolved in 1 mL ACN), 21 μL lithium ion solution (520 mg Li-TFSI dissolved in 1 mL ACN), and shake thoroughly. After the substrate cools to room temperature, evenly coat 35 μL of the solution on its surface at a speed of 4000 rpm, an acceleration of 2000 rpm / s, and a time of 20 s.

[0043] 5) Preparation of metal back electrode: A layer of 80nm Au electrode is evaporated on the surface by an evaporator to form a complete device.

[0044] The perovskite solar cell prepared in this experiment was tested under the conditions of one light intensity and a test area of ​​0.11 cm 2 The test light source is AAA level. The results show that the battery reverse scanning photoelectric conversion efficiency is 21.22%, with an open circuit voltage of 1092mV and a short circuit current of 24.38mA / cm 2 , the fill factor is 0.80; the forward scanning photoelectric conversion efficiency of the battery is 12.84%, with an open circuit voltage of 999mV and a short circuit current of 24.43mA / cm 2 , the filling factor is 0.53.

[0045] Embodiment 3:

[0046] Except for the preparation of the SnO2 electron transport layer, the remaining steps refer to Example 2: Take solution C and put it into a clean glass container, put in the cleaned FTO glass and seal it; heat it in a 90°C oven until an obvious Tyndall effect occurs, cool it with running water, take it out and wash to remove excess SnO2 particles on the surface, then wipe the back of the glass substrate to remove the SnO2 particles attached to the back, blow it dry with an air gun, and then place it on a hot table for annealing at 150°C for 1 hour.

[0047] The perovskite solar cell prepared in this experiment was tested under the conditions of one light intensity and a test area of ​​0.11 cm 2 The test light source is AAA level. The results show that the battery reverse scanning photoelectric conversion efficiency is 23.30%, with an open circuit voltage of 1112mV and a short circuit current of 24.55mA / cm 2 , the fill factor is 0.82; the forward scanning photoelectric conversion efficiency of the battery is 19.17%, with an open circuit voltage of 1123mV and a short circuit current of 24.82mA / cm 2 , the filling factor is 0.19.

[0048] Embodiment 4:

[0049] Except for the preparation of the SnO2 electron transport layer, the remaining steps refer to Example 2: Take solution D and put it into a clean glass container, put in the cleaned FTO glass and seal it; heat it in a 100°C oven until an obvious Tyndall effect occurs, cool it with running water, take it out and wash to remove excess SnO2 particles on the surface, then wipe the back of the glass substrate to remove the SnO2 particles attached to the back, blow it dry with an air gun, and then anneal it on a hot stage at 150°C for 1 hour.

[0050] The perovskite solar cell prepared in this experiment was tested under the conditions of one light intensity and a test area of ​​0.11 cm 2 The test light source is AAA level. The results show that the battery reverse scanning photoelectric conversion efficiency is 21.21%, with an open circuit voltage of 1100mV and a short circuit current of 24.01mA / cm 2 , the fill factor is 0.80; the forward scanning photoelectric conversion efficiency of the battery is 11.33%, with an open circuit voltage of 1005mV and a short circuit current of 24.04mA / cm 2 , the filling factor is 0.18.

[0051] Attached Figure 1 The electron scanning microscope images of the SnO2 nanofilm materials obtained in Examples 1 and 3, wherein A is the SnO2 nanofilm prepared in Example 1; B is the SnO2 nanofilm prepared in Example 3. It can be seen from Figure A that the tin oxide electronic layer completely covers the FTO, without obvious holes, but with a small amount of particles; the SnO2 nanofilm prepared in Figure B is smoother and more uniform, with no holes, and is superior to the SnO2 nanofilm prepared in Figure A in terms of morphology.

[0052] Attached Figure 2 The scanning electron microscope images of the perovskite films obtained in Examples 1 and 3 are shown, wherein A is the perovskite film prepared in Example 1; B is the perovskite film prepared in Example 3, and the average size of the grains in B increases. The increase in grain size reduces the grain boundaries with more defects, which is beneficial to improving the photovoltaic performance of the device.

[0053] Attached Figure 3 Steady-state output diagram of the perovskite solar cell obtained in Examples 1 and 3 at the maximum power point. The star-shaped mark indicates the steady-state output of the device prepared in Example 3 at the maximum power point, which is better than the device prepared in Example 1 (circle mark). The steady-state output under continuous illumination indicates that the device prepared in Example 3 has good long-term illumination stability.

Claims

1. A method for preparing an electron transport layer of a perovskite solar cell, characterized in that The following steps are involved: The UV treated FTO glass was immersed in Sn 4+ The mixture is placed in a diluent and sealed, heated in a forced air drying oven until an obvious Tyndall effect is produced, cooled sufficiently with running water, taken out for cleaning, and annealed to obtain a SnO2 electron transport layer; The Sn 4+ The dilutions were prepared as follows: Anhydrous SnCl4 and deionized water were mixed in a volume ratio of 3:7, stirred at 0-5 °C for 12-24 h, and the resulting mixed solution was diluted 18-20 times with deionized water; Add 180 - 1020 mg NH4Cl to 100 mL of dilution solution, then add appropriate amount of HCl and refrigerate for later use.

2. The method for preparing the electron transport layer of a perovskite solar cell according to claim 1, characterized in that The temperature of the blast drying oven is 80-100 ℃, and the heating time is 1.5-2.5 h.

3. The method for preparing the electron transport layer of a perovskite solar cell according to claim 1, characterized in that The annealing temperature is 150-170 ℃, and the annealing time is 0.5-1.5 h.

Citation Information

Patent Citations

  • Preparation method of stable and efficient perovskite solar cell

    CN111864084A